The Improvement Positive Attitudes Towards Environmental Mastery Through Group Guidance Role Playing Techniques. - Astri Febriyanti; Shinta Mayasari; Moch Johan Pratama (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The problem of this research is the students who have negative attitude in environmental mastery at school. The problem is whether the group guidance for role playing techniques can improve students positive attitude towards SMA Al-Azhar 3 Bandar Lampung. The objective of the research is to improve students positive attitudes towards psychological well-being, especially the dimension of environmental mastery. The quasi eksperimen design untreated control group design with dependent pre-test and posttest was used in this method. The subject of the research were 10 experimental group and 10 control group. Data collection techniques use a environmental mastery scale. The results showed that attitudes towards the environmental mastery of students in schools could be improved through group guidance techniques for role playing techniques, this was shown by the Mann Whitney test results. The results of statistical analysis showed value (Sig.) 0.000 0.05 the Ho was rejected by Ha accepted.Masalah penelitian ini adalah siswa yang memiliki sikap negatif terhadap environmental mastery di sekolah. Permasalahannya adalah “apakah layanan bimbingan kelompok teknik role playing dapat meningkatkan sikap positif siswa terhadap environmental mastery pada siswa kelas XI SMA Al-Azhar 3 Bandar Lampung. Tujuan penelitian untuk meningkatkan sikap positif siswa terhadap kesejahteraan psikologis khususnya dimensi Environmental mastery. Metode yang digunakan dalam penelitian ini adalah quasi eksperimen desain untreated control group design with dependent pre-test and posttest. Subjek penelitian yaitu 10 orang kelompok eksperimen dan 10 orang kelompok kontrol. Teknik pengumpulan data menggunakan skala sikap environmental mastery. Hasil penelitian menunjukkan bahwa sikap terhadap environmental mastery siswa di sekolah dapat ditingkatkan melalui layanan bimbingan kelompok teknik role playing, hal ini ditunjukkan hasil uji Mann Whitney. Hasil analisis statistik menunjukkan nilai (Sig.) 0,000 0,05, maka Ho ditolak Ha diterima.Kata kunci: bimbingan kelompok, sikap positif, teknik bermain peran